Customer Satisfaction on Islamic Housing Loan: A Study in Nilai Township - Woon, Tah Therk (2014)
Islamic banking had been operated in the world for around four decades and it has become one of the fastest growing industries. While having the term “Islamic” banking, Islamic banking operates their businesses using the rules and principles of Sharia’h. Due to the increase in housing development projects, the application of housing loan increases as well. As both conventional banks and Islamic banks offer the housing loan products, some researchers pointed out that customer in Malaysia are satisfied with the housing loan provided by the Islamic banking while other researchers commented that customers in Malaysia are not satisfied with the Islamic housing financing. Therefore, the objective of this study is to find out what are the factors that influence the customer satisfaction of Islamic housing loan in Malaysia. Quantitative method will be used while 250 questionnaires will be distributed to the respondents in public area such as banks and cafeteria. The respondents are of individuals that are 18 years and above who had or currently taking housing loan in Islamic banks. Of the 250 questionnaires distributed, 220 were completed and returned. The data will be analyzed using SPSS software version 20. Factor analysis and Reliability testing will be conducted to test the validity and reliability of the questions before proceeding in analyzing the data. In order to check the relationship and significance of the independent variables to the dependent variable, correlation, linear regression, and multiple regression analysis were used. The results pointed out the service quality, product quality, trust, and perceived value will influence the customer satisfaction of Islamic housing loan in Nilai. On the other hand, religion has tested to have no relationship with the customer satisfaction of Islamic housing loan in Malaysia. Recommendations like trainings, 10 minutes queue system, competitive products, and penalties for miss selling staffs can be done by Islamic banks while government can encourage more of Islamic banks to be established in Malaysia.